Buku kedominikanan : Untuk TK A Semester 1 & 2 /Yohana Agustine B, Sri Handayani, Sr. M. Theresiana ; editor, Sr. Serafine...[et.al] ; ilustrator, Yohanes Robertus - YOHANA AGUSTINE B; Sri Handayani; Theresiana, Sr. M; Yohanes Robertus (St. Dominic Publishing, 2015)
v, 75 hlm. : ilus. ; 24 cm.